2014
DOI: 10.1017/s0033583514000080
|View full text |Cite
|
Sign up to set email alerts
|

NMR structures of membrane proteins in phospholipid bilayers

Abstract: Membrane proteins have always presented technical challenges for structural studies because of their requirement for a lipid environment. Multiple approaches exist including X-ray crystallography and electron microscopy that can give significant insights into their structure and function. However, nuclear magnetic resonance (NMR) is unique in that it offers the possibility of determining the structures of unmodified membrane proteins in their native environment of phospholipid bilayers under physiological cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
30
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 206 publications
(420 reference statements)
0
30
1
Order By: Relevance
“…Challenges associated with studying membrane proteins called for a combination of solution and solid-state NMR experiments [25]. We found that the deletion of Arg14 slightly alters the transmembrane domain of the protein, as well as induces a pronounced shift of the conformational equilibrium of the cytoplasmic domain toward the membrane-detached R state.…”
Section: Introductionmentioning
confidence: 99%
“…Challenges associated with studying membrane proteins called for a combination of solution and solid-state NMR experiments [25]. We found that the deletion of Arg14 slightly alters the transmembrane domain of the protein, as well as induces a pronounced shift of the conformational equilibrium of the cytoplasmic domain toward the membrane-detached R state.…”
Section: Introductionmentioning
confidence: 99%
“…The three basic approaches to obtaining high resolution – motional averaging, spin dilution, and spin manipulation - are used in solid-state NMR studies of membrane proteins. It is worth noting that membrane proteins require the full range of solid-state NMR methods and instrumentation, and this accounts for the relatively long development period from the first double-resonance spectra of a liposome sample to the complete structures of membrane proteins that are now being determined [21]. …”
Section: High Resolution Solid-state Nmrmentioning
confidence: 99%
“…Our primary research interest is in structure determination of membrane proteins in their native environment of phospholipid bilayers (Opella 2013) (Radoicic et al 2014). However, on the path towards this goal, aspects of membrane protein sample preparation and, to some extent, experimental methods are first worked out with micelle (Mesleh et al 2003), bicelle (Son et al 2012), or nanodisc (Park et al 2011a) samples that are tractable for solution NMR.…”
Section: Introductionmentioning
confidence: 99%